Financial protection in health: updates for Mexico to 2014 - Felicia Marie Knaul; Héctor Arreola-Ornelas; Oscar Méndez-Carniado (Instituto Nacional de Salud Pública, 2016)
Objetive. Document financial protection in health in Mexico up to 2014. Materials and methods. We update the measures of impoverishing and catastrophic health expenditure to 2014, to analyse shifts since the implementation of the System for Social Protection in Health and the Seguro Popular using time series data from the Household Income and Expenditure Survey. Results. Between 2004 and 2014 there has been a continued improvement in levels of financial protection. Excessive expenditure reached its lowest point: -2.0% in 2012 and 2.1% in 2014. Impoverishing expenditure dropped to 1.3% in 2004, compared to 0.5% in 2014, and catastrophic expenditures from 2.7% to 2.1%. Conclusions. The time series of data on financial protection show a clear pattern of improvement between 2000 and 2014 and level off and low levels in 2012 and 2014. Still, levels continue to be relatively high for households in the poorest quintile, in rural areas and with an elderly person.